Implementasi Human Resource Scorecard Untuk Pengukuran Kinerja Karyawan Pada Kasus Perusahaan Di Indonesia - Stefanus Dony Mahendra (JEMAP, 2020)
Human Resource Scorecard is a tool used to measure organizational performance against the strategic goals set by a company. This research aims to determine the step of application Human Resource Scorecard for Employee Performance Measurement. The method of this research consists of Planning (Explanation of Research Objectives), Research Identification (Determine of Criteria Selection of Research Articles), Selection of Primary Studies (Selection of research articles using keyword criteria already determined). The keyword used is “HR Scorecard”. There are 2 (two) selection criteria: Inclusion criteria, which include: Research articles identified using keyword, Research articles that answer a research question, and Exclusion criteria, which includes: articles not in full text, research articles that use the HR Scorecard not to measure performance, research article with case studies on companies not located in Indonesia.  The result of this study of HR Scorecard implementation are: determining business processes, calculating the weight of each perspective using Analytical Hierarchy Process, create a hierarchy problem that is used to identify complex problem into a subsystem, determine priorities, do synthesis, measuring consistency, calculate consistency ratio, checking the consistency of the hierarchy, calculate scoring system, give recommend for the company.